Payment for Environmental Services in Nepal (A Case Study of Shivapuri National Park, Kathmandu, Nepal) - Kunwar, Kamal Jung (The Initiation, 2010)
With a view to highlight the issues of Payment for Environmental Services (PES) in Nepal, the paper aims at providing information on possible environmental goods and services rendered by the Shivapuri National Park (ShNP), Kathmandu. It also endeavors to explore the policy issues with regards to PES in Nepal. Secondary information was obtained through published and unpublished literatures and office records of ShNP whereas primary information was generated through various Rapid Appraisal tools; such as informal discussion with park officials, semi-structured interview, field observation etc. Despite the ShNP's role in providing environmental goods and services to the dwellers of Kathmandu metropolitan, the local inhabitants have not been benefited from such services. There has been low level of awareness on the issues such as environmental goods and services and possible benefits to be obtained and its equitable sharing. It is the dire need that policy should focus on these issues so that all the stakeholders could be benefited from the conservation and management of protected areas and forests in the country. Key Words: Payment for environmental services, Shivapuri national park, Upstream and downstream relationship, Benefit sharing, Free riders. DOI: 10.3126/init.v2i1.2525 The Initiation Vol.2(1) 2008 pp63-72